Green technologies competition and uncertainty: a Monte Carlo analysis of optimal biofuels supply choices for France. (December 2017) - Assoumou, Edi; Hugues, Paul; Maïzi, Nadia
Abstract: A timely development and diffusion of green technologies is widely recognised as a key element of an effective transition to a low carbon future. This is in particular the case in the transport sector where several low carbon options have been developed as substitute to oil products. However, green technologies do not only compete against conventional ones but also against each over. In this paper we investigate the conditions of such a competition in the biofuel sector. Our methodology uses a long term and technology rich model to describe the cost competiveness of several biofuel generation pathways. Using a Monte Carlo approach we then discuss the long term interaction between first, second, and third generation technologies.